Knowledge management : does the organizational culture matter? - Md. Nor, Khalil (Faculty of Management and Human Resource Development, 2006)
Individuals and organizations have begun to appreciate the increasingly important role of knowledge in the present competitive environment. For years organizations have coded, stored, and transmitted knowledge. However, the current advancement of information technology has made the tasks much easier to accomplish. Through information technology, the task of capturing, storing, and sharing the organizational knowledge can be done more systematically and efficiently. However, we believe that the utilization of information technology alone in the knowledge management does not guarantee its success. The author argues that the success of knowledge management, in particular the creation and sharing of tacit knowledge is also influenced by organizational culture. It is hypothesized that certain dimensions of organizational culture encourage the creation and sharing of tacit knowledge. In this paper, the author discusses knowledge, knowledge management, knowledge management system, knowledge sharing and creation, and national and organizational culture. Finally, the author provides four propositions and suggest an empirical test for them